2021
DOI: 10.1039/d1gc02430b
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the environmental sustainability of solvent-less fatty acid ketonization to bio-based ketones for wax emulsion applications

Abstract: The environmental and economic challenges currently faced by the wax market may be addressed by the use of sustainable bio-based alternatives. Hereto, ketonization of vegetable oils and animal fats is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 73 publications
0
21
0
Order By: Relevance
“…9 Recent life cycle analysis of the pathway studied in this work, VFA upgrading to sustainable aviation fuel (SAF) via sequential ketonization and hydrotreating, found that the process has a carbon emissions intensity below zero (−55 g CO 2eq MJ −1 ) due to avoided methane emissions otherwise generated when wet waste is landfilled. 10 Life-cycle analyses of VFA upgrading to diesel blendstocks 11 and fatty acid upgrading to waxes 12 and surfactants 13 also show that valorization of waste acids for fuels and chemicals results in substantial carbon intensity reductions. Thus, upgrading of wet waste-derived VFAs for use as aviation fuel blendstocks is a promising decarbonization pathway.…”
Section: Introductionmentioning
confidence: 99%
“…9 Recent life cycle analysis of the pathway studied in this work, VFA upgrading to sustainable aviation fuel (SAF) via sequential ketonization and hydrotreating, found that the process has a carbon emissions intensity below zero (−55 g CO 2eq MJ −1 ) due to avoided methane emissions otherwise generated when wet waste is landfilled. 10 Life-cycle analyses of VFA upgrading to diesel blendstocks 11 and fatty acid upgrading to waxes 12 and surfactants 13 also show that valorization of waste acids for fuels and chemicals results in substantial carbon intensity reductions. Thus, upgrading of wet waste-derived VFAs for use as aviation fuel blendstocks is a promising decarbonization pathway.…”
Section: Introductionmentioning
confidence: 99%
“…However, their molecular composition is suitable for C−C coupling to renewable C 23 −C 35 "wax" ketones. 11 They can be used directly as end products 12 or may serve as intermediates to undergo hydrodeoxygenation and hydroisomerization reactions for the synthesis of bio-based paraffinic waxes and lubricants. 13−16 Ultimately, they can serve as platform molecules for a wide array of functionalized compounds such as amines, alcohols, sulfonates, olefins, etc.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this context, a combined green chemistry and life cycle assessment (LCA) analysis study on a dedicated liquid-phase fatty acid ketonization process with anatase TiO 2 demonstrated that its use significantly contributes to the overall environmental burden of wax ketone production. 12 More specifically, for the production of 1 kg of ketone bio-wax product, 0.03 kg of TiO 2 catalyst was required, of which the latter showed substantial contributions to multiple LCA impact categories, viz., 2.2% climate change impact, 3.7% freshwater consumption, 43% freshwater eutrophication, 16% human toxicity, 16% terrestrial acidification, and 10% terrestrial ecotoxicity. These impacts are a result of the environmental footprint of the anatase TiO 2 fabrication process and moderate ketonization activity.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations